Atividade Biológica De Um Novo Triterpeno Isolado De Guarea Cannata (Meliaceae) - Pereira Júnior, Orlando Libório (Acta Amazonica, 2020)
From the bark of Guarea carinata was isolated as main constituent a diacetilated triterpen (I) of protolimonoids type, derived from apo-tirucalol, that showed antifeedant activity in biological control of Urbanus acawoios(Lepidoptera,Hesperiidae).